(untitled) (Research, Society and Development, 2025)
The consequences of increased life expectancy imply an increased incidence of chronic and neurodegenerative diseases, particularly Alzheimer’s disease, a major public health challenge. Among the associated pathophysiological mechanisms, dysfunction of the hypothalamic-pituitary-adrenal axis and prolonged exposure to high cortisol levels can promote neurotoxic effects in the hippocampus, a brain region crucial for memory and rich in glucocorticoid receptors. This study aimed to investigate, through an integrative review, the relationship between serum cortisol levels and hippocampal atrophy in the elderly, bringing together pathophysiological foundations and empirical evidence, as well as identifying research gaps. The literature search was conducted in PubMed, PsycINFO, SciELO, LILACS, and the Virtual Health Library databases, using specific descriptors and previously defined inclusion and exclusion criteria. The selection process followed stages of screening, reading, and critical analysis, with standardized data extraction. A total of 274 studies were identified, of which 82 were excluded due to duplication and 170 for not meeting the methodological and thematic criteria, leaving only one eligible study. The results reveal a significant scarcity of up-to-date, high-quality research on the topic, despite its global relevance. The integrated analysis indicates that interventions that reduce chronic exposure to cortisol or enhance hippocampal function, such as environmental or physical stimuli, may have a protective effect on brain aging. We conclude that robust longitudinal and experimental investigations are needed to deepen the understanding of this relationship and support preventive strategies for cognitive decline in older adults.